Edukasi Dan Aksi Bersih Pantai: Meningkatkan Kesadaran Masyarakat Pesisir Terhadap Kebersihan Laut - Fatoni, Fatoni; Alimsyah, Andi Saiful; Alim, Bahrul; Raswadi, Mohammad Dika; Butsiarah, Butsiarah (Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract The problem of waste in coastal areas is increasing due to low public awareness of the cleanliness of the marine environment. Waste that accumulates on beaches and coastal waters not only pollutes the ecosystem, but also threatens the lives of marine biota and the welfare of communities that depend on the fisheries and tourism sectors. This community service activity aims to increase awareness and participation of coastal communities in maintaining environmental cleanliness through the